1997
DOI: 10.1021/ja962676t
|View full text |Cite
|
Sign up to set email alerts
|

Raman and Infrared Spectra of (2‘S)-[2‘-2H]Thymidine:  Vibrational Coupling between Deoxyribosyl and Thymine Moieties and Structural Implications

Abstract: The thymidine stereoisotopomer, (2′S)-[2′-2 H]thymidine, which incorporates deuterium in the S configuration at the furanosyl 2′ carbon, has been synthesized and its vibrational spectra have been recorded and compared with those of normal thymidine. Infrared and Raman spectra were collected from crystalline powders, the latter using 1063-and 514.5-nm excitations; ultraviolet resonance-Raman spectra were collected from aqueous solutions using 244-nm excitation. The results show, remarkably, that virtually all n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 19 publications
(56 reference statements)
7
68
0
Order By: Relevance
“…The parent band has been assigned to a skeletal deformation of the pyrimidine ring that is coupled with both in-phase bending of the C2AO and C4AO carbonyl groups and distortion of the furanose ring. 36 The observed difference band near 665 cm Ϫ1 may reflect the greater propeller twist noted above for base pairs of poly(dA-dT)⅐poly(dA-dT) than for AT pairs in genomic DNA. It has also been demonstrated previously that a change in deoxynucleoside conformation can have a dramatic effect on the intensity of this band.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The parent band has been assigned to a skeletal deformation of the pyrimidine ring that is coupled with both in-phase bending of the C2AO and C4AO carbonyl groups and distortion of the furanose ring. 36 The observed difference band near 665 cm Ϫ1 may reflect the greater propeller twist noted above for base pairs of poly(dA-dT)⅐poly(dA-dT) than for AT pairs in genomic DNA. It has also been demonstrated previously that a change in deoxynucleoside conformation can have a dramatic effect on the intensity of this band.…”
mentioning
confidence: 90%
“…The carbonyl group stretching vibrations of thymine (C2AO and C4AO), guanine (C6AO), and cytosine (C2AO) are expected to give strong Raman bands in the 1600 -1750 cm Ϫ1 region and unambiguous assignments have been developed from studies of model compounds. 28,[33][34][35][36] Figure 2 shows that thymine carbonyls produce intense bands at 1652 and 1672 cm Ϫ1 , whereas the guanine C6AO mode at 1713 cm Ϫ1 is only moderately intense. Conversely, the cytosine C2AO mode near 1680 cm Ϫ1 is extremely weak.…”
mentioning
confidence: 99%
“…The cytosine vibration is sensitive to deputation exocyclic substitution while the phosphodiester vibration is less sensitive to deputation. The thymidine vibration, which involves both significant contribution from deoxyribose ring and dominant contribution from the thymine vibration, is sensitive to C2' deuteration (Tsuboi et al, 1997). The appearance of the cytosine vibration at higher frequency at 790 cm…”
Section: Resultsmentioning
confidence: 99%
“…Tsuboi et al have observed similar behavior for this mode in both IR and Raman studies in which the C2Ј of the deoxyribose moiety was deuterated, thereby uncoupling these two vibrations. 39 Another deoxyribose band at 1323 cm Ϫ1 in ct-DNA (Figure 4, 30°C) or 1321 cm Ϫ1 (Figure 6, 19°C) shifts up to its uncoupled frequency of ϳ1325 cm Ϫ1 . 17,22 There is no change in bandwidth and the intensity increase for this mode occurs only at 30°C.…”
Section: Comparison Of the Deoxyribose Vibrational Modes Between Dna mentioning
confidence: 99%
“…21,22,38,39 The band at 1274 cm Ϫ1 in ct-DNA is assigned to a deoxyribose mode and is normally relatively weak when coupled to T. 39 Upon binding of Blm this mode becomes almost 50% more intense, becomes broader and this band shifts to a frequency of ϳ1270 cm Ϫ1 . 17,39 This is a pattern seen not only at 30 but at 19°C (Figure 6). Tsuboi et al have observed similar behavior for this mode in both IR and Raman studies in which the C2Ј of the deoxyribose moiety was deuterated, thereby uncoupling these two vibrations.…”
Section: Comparison Of the Deoxyribose Vibrational Modes Between Dna mentioning
confidence: 99%